Cost Analysis of Skyline-assisted Felling Technique in Private Forests in Probolinggo, Indonesia - Budiaman, Ahmad; Hardjanto; Natalia, Yohana (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
Tree felling is an important component of the forest harvesting system. A skyline-assisted felling technique (locally known as the ‘sandat’ felling technique) is used in private forest harvesting in Probolinggo, East Java, Indonesia, as an alternative to the conventional felling technique. This felling technique is used in private forests planted with an agroforestry pattern. Private forest farmers have recognized the technique as an effective way to protect multi-purpose tree species, especially coffee plants, but the technique’s efficiency is not yet known. The study analyzed the costs and productivity of sandat felling techniques in private forests planted with agroforestry patterns in Probolinggo. Working time studies, branch-free height, and breast height diameter measurements were carried out to calculate felling costs and productivity. The present value cost function was developed to compare the costs of sandat felling techniques with conventional felling techniques. The study showed that the productivity of sandat felling techniques was lower than conventional felling techniques. In contrast, the operating costs of sandat felling techniques were higher than those of conventional felling techniques. The operating cost per m3 rose by 20%. Additional operating costs for sandat felling techniques were incurred for procuring ropes and installing and uninstalling skyline. The felling costs will decrease with the felling team's increasing experience and skill. Keywords: agroforestry, costs analysis, felling techniques, private forests, sandat felling